Supersymmetry - Fabiano, Nicola (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: Supersymmetry is a symmetry of the Lagrangian that goes beyond Lie groups. It allows the exchange of bosons and fermions. The most important model is the Minimal Supersymmetric Standard Model, or MSSM.Methods: Supercharge algebra, superfields, Grassmann numbers, and the Berezin integral.Results: Supersymmetric transformations are global, i.e., they do not depend on spacetime coordinates. In the case of Supergravity, they are local.Conclusion: Supersymmetric models, and MSSM in particular, could de- scribe particle physics better than the Standard Model.
Keywords: supersymmetry; minimal supersymmetric standard model